2022
DOI: 10.1038/s41467-022-34599-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased slow dynamics defines ligandability of BTB domains

Abstract: Efficient determination of protein ligandability, or the propensity to bind small-molecules, would greatly facilitate drug development for novel targets. Ligandability is currently assessed using computational methods that typically consider the static structural properties of putative binding sites or by experimental fragment screening. Here, we evaluate ligandability of conserved BTB domains from the cancer-relevant proteins LRF, KAISO, and MIZ1. Using fragment screening, we discover that MIZ1 binds multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…F9 and F125 are crucial for BTB domain stability and binding to FBXO22 (Figure 1, Supplementary Figure 2c-e). When we probed the conformational flexibility of the BACH1 BTB domain by NMR, we observed a very rigid backbone throughout the protein on the picosecond to nanosecond timescale by { 1 H}, 15 N-heteronuclear Overhauser effect ( het NOE) NMR spectroscopy (Figure 4c), similar as previously observed for other BTB dimers 19 . Hydrogen deuterium exchange (HDX) NMR experiments suggest a very tight BTB dimer, as demonstrated by slow HDX in the dimer interface comprising α1, α2 and α5 (Figure 4d).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…F9 and F125 are crucial for BTB domain stability and binding to FBXO22 (Figure 1, Supplementary Figure 2c-e). When we probed the conformational flexibility of the BACH1 BTB domain by NMR, we observed a very rigid backbone throughout the protein on the picosecond to nanosecond timescale by { 1 H}, 15 N-heteronuclear Overhauser effect ( het NOE) NMR spectroscopy (Figure 4c), similar as previously observed for other BTB dimers 19 . Hydrogen deuterium exchange (HDX) NMR experiments suggest a very tight BTB dimer, as demonstrated by slow HDX in the dimer interface comprising α1, α2 and α5 (Figure 4d).…”
Section: Resultssupporting
confidence: 74%
“…Most notably, we found that cysteine modifications destabilized BACH1 BTB and induced a ligase shift, similarly to what we observed for genetic perturbations. In an effort to label native cysteines in BACH1 BTB with Bromo-1,1,1-trifluoroacetone (BTFA) for 19 F NMR spectroscopy studies (Supplementary Figure 13b and c, we noticed loss of binding of modified BACH1 BTB to SKP1-FBXO22 in fSEC experiments. By contrast, complex formation with SKP1-FBXL17 was observed (Figure 7b).…”
Section: Btb Domain Destabilization Redirects Bach1 From Fbxo22 To Fb...mentioning
confidence: 99%
“…This region of MIZ1 seems to be an intrinsically disordered region that can form a beta strand that participates in a beta sheet structure that has also been reported to mediate the formation of MIZ1 tetramers [75]. The same region was identified as a good site for ligand binding in a small molecule fragment screen due to its high mobility [76].…”
Section: Association With Corepressorsmentioning
confidence: 99%